Nutritional Status in Breast and Cervical Cancer Survivors: Differences in Each Stage of Survivorship - Ni Putu Wulan Purnama Sari (Journal of Global Pharma Technology, 2020)
Objective: Nutrition is one important physical aspect supporting the achievement of optimum quality of life (QOL) in cancer survivors. This study aimed to 1) compare and analyze the differences in nutritional status between breast and cervical cancer survivors (BCS and CCS) generally, and between stages of survivorship specifically in both cases, and 2) determine the best predictor of nutritional status in both cases.  Method: This cross-sectional study involved 58 BCS and 47 CCS (n=105). The questionnaire of PG-SGA was used in data collection. Various statistical tests were used in data analysis (α<0.05). Result: Nutritional status was not significantly different between BCS and CCS (p=0.116), but significant differences found in activities and function between cases (p=0.040). In BCS, nutritional status was not significantly different between survivorship stages (p=0.068), which indicates that this aspect is stable/stagnant across the survival life span in this case. While in CCS, nutritional status was also not significantly different between survivorship stages (p=0.382), but the intake and physical exam were significantly different in this case (p=0.040 and p=0.008, respectively) which indicate that these two aspects change over time along with the survivorship stages in CCS. Body Mass Index (BMI) is the best predictor of nutritional status in BCS, which were accounted for 15.9% variance of nutritional status (R2=0.159); while weight loss is the best predictor of nutritional status in CCS, which were accounted for 49.6% variance of nutritional status (R2=0.496). Discussion: More significant predictors of nutritional status were found in CCS compared to BCS.Keywords: Breast cancer, Cancer survivors, Cervical cancer, Nutrition, Nutritional status.